سیمۆلۆژیای کاراکتەر لە ڕۆمانی (پەیکەرێک لەتۆزی دەباشیر)دا - محمد, میران جلال (Sulaimani Journal for Humanities, 2022)
This research will attempt to analyze the role and position of a type of a character in the novel of (a sculpture from the dust of a chalk). According to the principles of semiology method and in the method itself, the messages of professor (Philippe Hamon) in regard to researching of this type have been considered on the level of deep and surface structure. The novelist in this novel has exercised some new techniques and strategies from the organization and functioning movements of the characters through the angles of two directions: real and imaginations in their roles despite of leaving the text to criticize. This is a kind of exceeding and creating which has exceeded from the frame compared to many others which remained unanswered in other novels. The characteristics of (a sculpture from the dust of a chalk) are the main reason to choose it as a topic to work on it. According to one of the newest methods including semiology method which is now one of the productive common methods. It is used for the narrated texts in general and common in particular
Keywords: Novel; character; semiology; techniques; narrative